Functional, physicochemical, and structural properties of the hydrolysates derived from the abalone (Haliotis discus subsp hannai Ino) foot muscle proteins - Guiyan Li; Xiang Zuo; Xinlin Luo; Zhongqin Chen; Wenhong Cao; Haisheng Lin; Xiaoming Qin; Leiyan Wu; Huina Zheng (Food Chemistry: X, 2023)
This study was conducted to investigate functional, physicochemical, and structural properties of abalone foot muscle proteins (AFPs) and their hydrolysates (HAFPs) obtained using animal protease (HA), papain (HPP), and Protamex® (HP) at different time points. The HA-hydrolysate obtained after 0.5 h of treatment demonstrated the highest solubility at pH 7.0 (84.19%); the HPP-hydrolysate at 4 h exhibited the highest degree of hydrolysis (11.4%); the HPP-hydrolysate at 0.5 h had the highest oil holding capacity (2.62 g/g) and emulsion stability index (39.73 min), and the HP-hydrolysate at 4 h had the highest emulsifying activity index (93.23 m2/g) and foaming stability (91.45%); Regarding the physicochemical properties, the HPP-hydrolysates revealed the largest particle size, higher absolute zeta potential, and superior interfacial activity. Structural characterization demonstrated the enzymolysis-based changes in the composition and the secondary structure of the AFPs. These results provide practical support for the theoretical basis of the use of AFPs as a source of nutritive proteins in the food industry.